EFL HIGH SCHOOL STUDENTS’ STRATEGIES FOR REDUCING SPEAKING ANXIETY - Nugroho, Hafidz Satrio; Hapsari, Astri (The Journal Of English Teaching For Young And Adult Learners, 2024)
This research aims to investigate the strategies that EFL high school students use to overcome their speaking anxiety in the classroom context in the academic year 2022/2023. This study employed a qualitative method. The data were collected through interviews with three participants from a private secondary school in Yogyakarta and semi-structured interviews were conducted to gain strategies used by participants to cope with foreign language speaking anxiety. The data was analyzed using thematic analysis. The overall results show that the three participants experienced anxiety when carrying out learning activities in class, both when communicating, receiving evaluations, and when taking grades. In this study, it was also found that participants had strategies to overcome their EFL speaking anxiety (i.e., preparation, relaxation, peer seeking, and resignation), which could help them deal with EFL speaking anxiety in the classroom context. Therefore, with this strategy, students can have lower anxiety when carrying out learning activities in class. This research offers some ways to reduce anxiety and enhance classroom experiences. It emphasizes the need for further research on anxiety's broader impact and suggests the role of teachers in supporting students with speaking anxiety.